An Analysis of Positive Politeness Strategies on You Tube Video Entitled “Ariana Grande I Full Video” - Wel Son; Afriana Afriana (LPPM Universitas Putera Batam, 2023)
The aim of this research is to find and explain the occurrence of positive politeness strategies from You Tube video entitled “Ariana Grande I Full Video”. In analyzing the data, researchers took the theory of positive politeness strategies in the scope of Pragmatics by Brown & Levinson (1987) that consists 15 strategies. Descriptive qualitative method was applied by researchers in this research. In collecting data, researchers took observational method, such as watching and listening careful to the video, finding the words that contain the occurrence of positive politeness, collecting the data from the video, divide them based on positive politeness strategies, analyze the words, and explain the result of the analysis. After done doing the analysis, researchers found 68 phenomenon that occur in 10 positive politeness strategies, they are 3 occurrence of the first strategy (Notice, attending to hearer), 13 occurrence of the second strategy (Exaggerating (Showing interest, approving, and give sympathy to hearer)), 8 occurrence of the fourth strategy (Using in group identity marker), 21 occurrence of the fifth strategy (Seeking agreement), 3 occurrence of the sixth strategy (Avoid disagreement), 10 occurrence of the seventh strategy (Presupposing, raising, or asserting common ground), 1 occurrence of the eighth strategy (Giving joke), 1 occurrence of the twelfth strategy (Including or getting both speaker and hearer into the activity), 7 occurrence of the thirteenth strategy (Giving or asking for reason), and 1 occurrence of the fifteenth strategy (Giving gifts to H in the form of goods, sympathy, understanding, and cooperation).